Prevention and early interventions in mental health: an international perspective - Irarrázaval, Matías; Prieto, Fernanda; Armijo, Julio (Acta Bioethica, 2016)
Mental diseases are common, chronic and disabling, representing a problem in public health of importance in our country and in the world. For most common mental diseases, currently we dispose of medical and psycho social interventions with proven efficacy. Nevertheless, these are not sufficient yet, and their availability does not diminish the morbidity and mortality produced by mental diseases. In order to solve this, a considerable effort has been carried out in the last 15 years to develop techniques of early detection for persons with high clinical risk to develop mental illness and precocious interventions to prevent or delay the progression of full illness. A greater emphasis in mental health and integrating mental health care in all relevant development programs will strengthen the general development effort, as well as it will ensure, for the first time, sustained attention to investment and research to the main world contributor to loss of productivity and disease burden.